ILLUSTRATION OF FAMILY MEMBER SMOKING HABIT IN ACUTE RESPIRATORY INFECTION (ARI) IN TODDLER AT BUNGAH HEALTH CENTER GRESIK DISTRICT - Lilis Zuhriyah (UNEJ e-Proceeding, 2017)
Background: The smoking habit of a family member without regard to the surrounding environment not only can cause problems for smokers themselves but also cause problems for other people, including a toddler who lives with them. One of the problems which often appears in young children due to the exposure of cigarette smoke is Acute Respiratory Infection (ARI). ARI in toddler is a major cause of toddler health care visits and toddler mortality in Indonesia. The purpose of this study is to describe smoking habit of a family member in ARI in the toddlers at the Bungah Health Center Gresik District. Methods: Samples of this study are 100 toddlers suffering from ARI and the technique which used is purposive sampling. This research employs the descriptive quantitative method and the instrument used is guttman scale with r table value is 0,36. Results: The results show that from 100 toddler respondents, male 56%, female 44%; aged ≤ 12 months 28%, 72% aged 13-59 months; malnourished nutrient status 6%, poor 15%, good 78%, overweight 1%; Mother’s last education, primary school 5%, junior highschool/equal 24%, senior highschool/equal 60%, 11% college; smoking habit of family members 73%, with no smoking habit of family members 27%; smoking habits without regard to the environment 58.90%, 41.10% attention to the environment (n = 73); 25.58% one smoker, more than one person 74.42% (n=43); mild smoker (30.24), moderate smoker 34.88%, 34.88% severe smoker (n=43). Conclusions: Conclusion is a large of number of toddlers with ARI, have a family with smoking habit. Keywords: ARI, Smoking habit of family member, Toddler